Seasonal variation of phycoerythrin chromophores of Synechococcus spp. in the East Sea/Japan Sea - Yona, Defri; Park, Mi Ok (Indonesian Journal of Natural Pigments, 2019)
The very small size of Synechococcus spp. as one important contributor of ocean primary productivity can be identified using its phycoerythrin pigment chromophores, phycourobilin (PUB) and phycoerythrobilin (PEB). Seasonal variation of the excitation (EX) ratio of PUB and PEB in the surface water of East Sea/Japan Sea was observed. This study aimed to describe the effects of environmental factors during different season to the excitation ratio of PUB and PEB contained Synechococcus spp. Summer and winter showed slightly similar distributional pattern with PUBEX:PEBEX ratio > 1, while PUBEX:PEBEX ratio < 1 could be found in autumn and spring. The results of this study showed seasonal patterns of phycoerythrin pigment from Synechococcus were highly related with variability of environmental factors. High light intensity during summer and high salinity during winter were the reasons of high PUB:PEB ratio of Synechococcus spp. Moreover, high PUB type of Synechococcus spp. was also dominated the offshore study areas as the result of higher water clarity compared to the one in the coastal areas.